Shakespeare and Marx - Egan, Gabriel (Oxford Shakespeare topics., 2004)
Marxist cultural theory underlies much teaching and research in university departments of literature and has played a crucial role in the development of recent theoretical work. Feminism, New Historicism, cultural materialism, postcolonial theory, and queer theory all draw upon ideas about cultural production which can be traced to Marx, and significantly each also has a special relation with Renaissance literary studies. This book explores the past and continuing influence of Marx's ideas in. work on Shakespeare. Marx's ideas about cultural production and its relation to economic production a.